PENGGUNAAN APLIKASI TEGUR SAPA GADGED PADA PEMBELAJARAN MENULIS - Sismanto (Al-Rabwah, 2021)
This study aims to know the preparation, implementation, and results of the application used in applying gadgets on how to write in grade 4. To overcome the difficulties learners face in writing, the teacher practised a learning model using scolds greet apps, which is a program application that connects voice to text and text to voice. Scolds application gadgets using colour note and greet applications gadget using voice aloud reader. The usage of scolds greet gadget apps can overcome students' difficulties in finding ideas and making easy-to-write concepts. To bring a positive change in the interest of learners in writing. The evidence can be seen from the recapitulation of marks in each meeting increased. The first meeting has an average of 7.83, the second meeting has 11.48, and at the third meeting, it has changed to 13.72. the results of questionnaires and interviews from 34 students only 12 people who like to write essays, after applied scold greet gadgets from 34 students, 28 learners to be like to write essays.